Agency, control, and means-ends about school performance in Lithuanian children (grades 4-6) - Šimulionienė, Roma (Psichologija, 2000)
This study examined beliefs about factors affecting school performance and about self-agency and control in Lithuanian children (grades 4-6, N = 379). Results revealed much intercultural convergence with the samples from other countries in children’s beliefs about the importance of effort, ability, luck and unknown factors as causes of school performance. The only difference we found was in the beliefs about the importance of teachers. Their ratings were the lowest. But at the same time the ratings of the accessability of teacher as a mean of school success were high (second after effort). The agency and control beliefs were moderately and highly correlated with school grades (r = 0,29-0,57). The fourth graders showed higher agency and control beliefs and the lowest correlations with school performance. These findings are interpreted as beeing affected by positive changes in Lithuanian school system.